A Focus of Rumenal Cancer in Kenyan Cattle - Plowright, W. (Nature Publishing Group, 1971)
A minimal incidence rate of 2·5% of rumenal cancer of cattle in the Nasampolai valley of Kenya Masailand has been established. Carcinoma of the oesophagus and oesophageal region of the stomach in two free-living giant forest hogs from the same area is reported. The high incidence of the bovine disease is thought to be associated with the abnormal forest grazing of the cattle. The possible aetiology of the disease is discussed.